Faktor-faktor yang Mempengaruhi Kerjasama Jangka Panjang untuk Meningkatkan Keunggulan Kompetitif Perusahaan - Cahyono, Joko (Jurnal Ilmu Ekonomi ASET, 2010)
The study was conducted in PT Meka Adipratama Semarang in which a turnoverdecline had been found due to the high business competition and the companyâs inefficientchannel of distribution. The research study was aimed at finding out reputation, trust,dependency, satisfaction, commitment, and communication factors towards long-termcooperations in order to develop the companyâs competitive excellence. Questionnaires andinterviews were used to learn about respondentâs perceptions on each variable. This is inaccordance with type and data resource used, i.e primary data. Meanwhile, for the analysistechnique, SEM with AMOS 5 program was applied to test the research model as well as theproposed hypothesis.The result shows empiric evidence that the variables used, i.e. reputation,trust, dependency, satisfaction, commitment and communication, have a positive and significantinfluence on long-term cooperations. By considering these factors, harmonious and beneficialcooperations can be achieved and the companyâs competitive advantage can be enhanced.Both the limitation and future research agenda will be further explained in the last chapter ofthis study.Keywords : reputation, trust, dependency, satisfaction, commitment communication, long-termcommunication, competitive advantage.